Intelligent CALL - Cornelia Tschichold (Routledge Handbook of Language Learning and Technology, 2016)
This chapter describes the provision of corrective feedback in Tutorial CALL, sketching the challenges in the research and development of computational parsers and grammars. The automatic evaluation and assessment of free-form learner texts paying attention to linguistic accuracy, rhetorical structures, textual complexity, and written fluency is at the centre of attention in the section on Automatic Writing Evaluation. Reading and Incidental Vocabulary Learning Aids looks at the advantages of lexical glosses, or look-up information in electronic dictionaries for reading material aimed at language learners. The conclusion looks at the role of ICALL in the context of general trends in CALL.